Improved Maturation Rate of Bovine Oocytes Following Sericin Supplementation in Collection and Maturation Media - F. A. Satrio; N. W. K. Karja; M. A. Setiadi; E. M. Kaiin; M. Gunawan; E. Memili; B. Purwantara (Faculty of Animal Science, Bogor Agricultural University, 2022)
Sericin is a water-soluble protein produced by silk cocoons and known to have antioxidant activity. This study is aimed to analyze the nuclear maturation and the quality of bovine oocytes in the collection and in vitro maturation (IVM) medium supplemented with sericin. Bovine oocytes were collected using a collection medium supplemented with sericin in 0 (control) concentrations, 0.1%, 0.5%, and 1%. Selected oocytes were then matured for 24 h at 38.5 oC in 5% CO₂ and evaluated for nuclear maturation. In the subsequent experiment, oocytes were collected and matured with or without 0.1% sericin at 38.5 oC in 5% CO2. Matured oocytes were counterstained with terminal deoxynucleotidyl transferase nick-end labeling (TUNEL) and Hoechst 33342. Matured oocytes were characterized by oocytes that reached the MII stage. The results showed that supplementation of 0.1% sericin in the collection medium increased the number of oocytes reaching the metaphase II (MII) stage compared to the control group (p<0.05). In the next experiment, sericin 0.1% in the collection and in vitro maturation media increased (p<0.05) the percentage of oocytes reaching the MII stage compared to control without sericin supplementation. Furthermore, the number of fragmented DNA in the oocytes showed no differences in all groups. It can be concluded that supplementation of 0.1% sericin in the collection and in vitro maturation media improved the nuclear status without affecting DNA fragmentation.